A Web-Based Computer Lab Management System: Case Study in Sekolah Kebangsaan Tikam Batu, Sungai Petani - Siti Fatimah, Baharum (2012)
This study will be conducted to manage the computer laboratory at school in a systematic and effective manner. A web-based computer lab management will be developed to provide facilities for teachers to make a reservation for using lab computer, to log the use of computer by students, and produce reports about the computer lab utilization to the management of school and education authority. Teachers do not have to wait on school hours for booking the computer lab. They can perform a reservation in anywhere and at any time term through the internet. Reports on the analysis of the use of computer laboratories will be submitted to the State Education Department (PPD) and others education authority periodically. This study will adapt automated analysis usage system for computer lab management system. The prototype of computer lab management system will be developed by using PHP and MySQL for ensuring the proposed model/methodology/approach/framework/system is workable. The system will be tested for usefulness at the computer laboratory in Sekolah Kebangsaan Tikam Batu. The web-based computer lab management system has potential to be implemented in other schools, which required laboratory management system to manage their facilities.